Answers

2015-08-06T18:54:51+08:00
Ex. of 9x²+15x+4     first multiply the 9 x 4=36, 12 x 3=36
ac=36
b=12 3
9x²+3x+12x+4
3x(3x+1)4(3x+1)
the answer is
     (3x+1)(3x+4)
0
2015-08-06T22:32:33+08:00
Example: 12x²+23x=-5 (its not in the standard form ax²+bx+c)
                                  ( so, we should rewrite it in the standard form)
12x²+23x-5=0 (Standard form)
FIRST WE FACTOR IT.
(3x+5) (4x+1) --> Factor
To solve: 3x*1= 3x
               5*4x=20x
Then ADD 3x + 20x =23x
VALUES OF X
3x+5=0
3x= -5
3     3
X= -5/3

4x+1
4x-1
4     4
X= -1/4
0